2017
DOI: 10.3389/fneur.2017.00484
|View full text |Cite
|
Sign up to set email alerts
|

Compromised Motor Dexterity Confounds Processing Speed Task Outcomes in Stroke Patients

Abstract: Most conventional measures of information processing speed require motor responses to facilitate performance. However, although not often addressed clinically, motor impairment, whether due to age or acquired brain injury, would be expected to confound the outcome measure of such tasks. The current study recruited 29 patients (20 stroke and 9 transient ischemic attack) with documented reduction in dexterity of the dominant hand, and 29 controls, to investigate the extent to which 3 commonly used processing spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 59 publications
0
20
0
1
Order By: Relevance
“…Despite the development of good EHC by teen years, peak EHC does not continue through adulthood (Rand and Stelmach, 2011; Engel-Yeger et al, 2012; Ebaid et al, 2017; Low et al, 2017). In the current study, those over the age of 40 increasingly made more errors, took longer, and demonstrated greater variability in performance as the decades progressed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the development of good EHC by teen years, peak EHC does not continue through adulthood (Rand and Stelmach, 2011; Engel-Yeger et al, 2012; Ebaid et al, 2017; Low et al, 2017). In the current study, those over the age of 40 increasingly made more errors, took longer, and demonstrated greater variability in performance as the decades progressed.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, those over the age of 40 increasingly made more errors, took longer, and demonstrated greater variability in performance as the decades progressed. The deterioration in motor control during adulthood is well-known (Rand and Stelmach, 2011; Engel-Yeger et al, 2012; Ebaid et al, 2017; Low et al, 2017). Adults undertaking the Purdue Pegboard test ( n = 7,834) showed a marked deterioration in dexterity with age (Tiffin and Asher, 1948), with similar outcomes on the more demanding Grooved Pegboard test ( n = 357, 16–70 years) (Ruff, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our ndings support that even after su cient strength recovery, braking performance in stroke is impacted by reduced movement precision. (37) and the measurement of motor accuracy can depend on visual information processing (38,39).…”
Section: Stroke Increases the Time Required To Apply Brakes During Simentioning
confidence: 99%